THE INFLUENCE OF EXTENSIVE READING STRATEGY AND READING INTEREST TOWARD STUDENTS’ READING COMPREHENSION OF ELEVENTH GRADE STUDENTS OF SMAN 1 TULUNG SELAPAN. - Nabilah Natasya; Tahrun Tahrun; Hanni Yukamana (Universitas PGRI Palembang, 2022)
The objectives of the study are to find out whether or not(1) There is significant influence of extensive reading towards students’ reading comprehension between those who have height reading interest and those who have low reading interest at the eleventh grade students of SMA Negeri 1 Tulung Selapan (2) There is significant influence of conventional reading strategy toward the eleventh grade students’ reading comprehension between who those have high reading interest and those who have low reading interest at the eleventh grade students of SMA Negeri 1 Tulung Selapan. (3) There is significant influence of extensive reading strategy and conventional reading strategy towards the eleventh grade students’ reading comprehension between those who have high reading interest and those who have low reading interest at the eleventh grade students of SMA Negeri 1 Tulung Selapan.(4) There is significant interaction effect of extensive reading strategy and reading interest on students’ reading comprehension at the eleventh grade students of SMA Negeri 1 Tulung Selapan. This study used Saphiro-Wilk test and it used Levene's test in testing the homogenity. It was found that the significance value for homogeneity test (Levene’s test) was 0.021 which is lower than 0.05, therefore the data was not considered homogeny, so the writers took the equal variances not assumed on t-test. Next, the significance value for t-test was 0.000. It showed that there was a significant difference of extensive reading strategy and no treatment reading strategy on the eleventh grade students’ reading comprehension who have low reading interest because the sig. value was lower than 0.05. That means the null hypothesis (Ho3b) is rejected.